2021
DOI: 10.1016/j.jbc.2021.100347
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II increases activity of the ClC-K2 Cl− channel in collecting duct intercalated cells by stimulating production of reactive oxygen species

Abstract: The renal collecting duct plays a critical role in setting urinary volume and composition, with principal cells transporting Na + and K + and intercalated cells mediating Cl − reabsorption. Published evidence implies Angiotensin II (Ang II) is a potent regulator of the collecting duct apical transport systems in response to systemic volume depletion. However, virtually nothing is known about Ang II actions on the basolateral conductance of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…27,28 We and others have shown that ClC-K2 is the dominant Cl − channel on the basolateral membrane of intercalated but not principal cells of the collecting duct. [29][30][31][32] However, little is known about the physiological roles of ClC-K2 in this segment.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 We and others have shown that ClC-K2 is the dominant Cl − channel on the basolateral membrane of intercalated but not principal cells of the collecting duct. [29][30][31][32] However, little is known about the physiological roles of ClC-K2 in this segment.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other epithelial tissues (such as the lung (4, 5) and intestine (6, 7)) there are limited in vitro systems that recapitulate the physiological function of the nephron, let alone the patterned collecting ducts (though a recent report demonstrated directed differentiation of human pluripotent stem cells into collecting duct epithelial cells (8)). To date, significant advances in our understanding of transport phenomena in the collecting ducts has relied on low-throughput methods such as perfused (9, 10) or split-open single tubules (11, 12), as well as transgenic animal models. Immortalized cell lines, such as mpkCCD cells, have been effective tools in understanding AQP2 regulation in PCs (13, 14), as well as amiloride-sensitive ENaC current (15, 16).…”
Section: Introductionmentioning
confidence: 99%